2023
DOI: 10.1071/hc22122
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to prescribing medicinal cannabis in New Zealand

Abstract: Introduction. The New Zealand Medicinal Cannabis Scheme (NZMCS) was established in April 2020 with the aim of expanding access to quality controlled medicinal cannabis products and developing a domestic medicinal cannabis industry. Yet, two years later, many patients report challenges in utilising the NZMCS, including physicians' reluctance to provide prescriptions for products. Aim. To explore the barriers and facilitators to prescribing medicinal cannabis in New Zealand. Methods. We conducted semi-structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Negative attitudes towards medicinal cannabis prescribers within the medical community was a novel barrier to prescribing identified in this study, demonstrating how social factors influence prescribing behaviours [45]. While some recent research has shown that practitioners from New Zealand are concerned about damaging their professional reputation by prescribing medicinal cannabis [43, 46], the present study is the first to document prescribing practitioners' experiences of judgement and disesteem within the profession.…”
Section: Discussionmentioning
confidence: 69%
“…Negative attitudes towards medicinal cannabis prescribers within the medical community was a novel barrier to prescribing identified in this study, demonstrating how social factors influence prescribing behaviours [45]. While some recent research has shown that practitioners from New Zealand are concerned about damaging their professional reputation by prescribing medicinal cannabis [43, 46], the present study is the first to document prescribing practitioners' experiences of judgement and disesteem within the profession.…”
Section: Discussionmentioning
confidence: 69%
“…Despite these challenges, in New Zealand, there is a burgeoning desire among patients to explore the putative benefits of cannabis therapeutics, as well as some interest by physicians (Gulbransen et al , 2020; Withanarachchie et al , 2023). This is evident in data generated via the Ministry of Health’s New Zealand Health Survey .…”
Section: Introductionmentioning
confidence: 99%
“…Previous New Zealand research, using an anonymous online convenience survey, found fewer than 5% of respondents got their cannabis products via a GP, with most still accessing cannabis via the underground market or being gifted it by family or friends (Rychert et al, 2020). Despite these challenges, in New Zealand, there is a burgeoning desire among patients to explore the putative benefits of cannabis therapeutics, as well as some interest by physicians (Gulbransen et al, 2020;Withanarachchie et al, 2023). This is evident in data generated via the Ministry of Health's New Zealand Health Survey.…”
Section: Introductionmentioning
confidence: 99%
“…Withanarachchie and colleagues interviewed 31 physicians (GPs, secondary care specialists, and cannabis clinicians) who had discussed medicinal cannabis with patients in the previous 6 months. 10 These doctors reported that their biggest barrier to prescribing was lack of clinical evidence supporting cannabis therapy, but the price of the products for patients and concerns about their professional reputation also limited their use. They were more likely to prescribe when all other treatment options had been exhausted.…”
mentioning
confidence: 99%